Estructuras y motivos del western en la road movie: Río Rojo vs. Las aventuras de Priscilla, reina del desierto - Pérez Rufí, José Patricio (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2007)
The present study analyzes in a concrete film, Howard Hawks’s Red River, some of the constants present in the genre of western, to apply these mentioned plot and thematic motives to a film placed between the comedy and the road movie, The adventures of Priscilla, queen of the desert. The aim is to state the presence of the least obvious structures though typical of a nowadays considered genre drawn to a close, the western, in other current films